PERMAINAN KANCING UNTUK PENINGKATAN PERKEMBANGAN KETERAMPILAN FISIK-MOTORIK ANAK USIA DINI - Clara Siti Sendari; Iin Indriani; Arifah A Riyanto; Dedah Jumiatin (IKIP Siliwangi, 2018)
One aspect of physical-motor development in early childhood is the muscles that affect the development of strength and motor skills (rough and smooth) which can be increased through learning activities or play activities that are varied, creative, and fun in accordance with the character of an active child, dynamic and enthusiastic. Button play is an activity of playing using button media that has a variety of shapes, colors and sizes, which are carried out or packaged in various ways or strategies, including inserting buttons into bottles, rooting, connecting ribbons, attaching buttons according to their shape and color, moving buttons using tweezers, which is done by walking or running. The action research conducted in this class aims to find out the improvement of the child's physical-motor skills development through the button game approach which is carried out in two cycles. The technique used in data collection is through assessment guidelines and observation sheets. Data obtained from the results of research using statistical analysis methods and description analysis. The study was conducted on 15 children at an early age. Data from the results of research and analysis showed an increase in the development of physical-motor skills in children as subjects of the study. This shows that the button game can improve the development of physical-motor skills in the early childhood group.